PENGARUH PENERAPAN SISTEM MANAGEMEN MUTU TERHADAP KINERJA MANAGERIAL YANG DIMODERASI OLEH SISTEM PENGUKURAN KINERJA DAN PENGHARGAAN - HARYO SUPARMUN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of the research was to obtain empirical evidence of the influence of the quality management system on managerial performance. In addition, the influence of performance measurement and reward system on the relationship between quality manage-ment system and managerial performance. The research used a questionnaire survey with respondents of manager of a manufacturing company in Jakarta and Bekasi. The results showed that the quality management system influence on managerial performance. While, performance measurement and reward system have not affect the relationship between quality management system and managerial performance.